The predictors and surgical outcomes of different distant metastases patterns in upper tract urothelial carcinoma: A SEER-based study - Hu, Xuan-han; Miao, Jia; Qian, Lin; Zhang, Da-hong; Wei, Hai-bin (Frontiers in Surgery, 2022)
The purpose of this study was to investigate the predictors of metastatic patterns of upper tract urothelial carcinoma (UTUC) and to analyze the surgical outcomes of different metastatic patterns of UTUC. Data on patients with UTUC from 2010 to 2017 were retrieved from the Surveillance, Epidemiology, and End Results Program (SEER) database. Kaplan–Meier analysis was applied to compare the patients’ survival distributions. Univariate and multivariate logistic regression was used to assess the specific predictors of site-specific metastases, while competitive risk regression was applied to estimate the predictors of cancer-specific mortality in patients with metastases. A total of 9436 patients were enrolled from the SEER database, of which 1255 patients had distant metastases. Lung metastasis (42.5%) was most common and patients with single distant lymph node metastasis had a better prognosis. Clinical N stage (N1, N2, N3) was the strongest predictors of the site specific metastatic sites. Renal pelvis carcinoma was more prone to develop lung metastases (OR=1.61, P<0.01). Resection of the primary tumor site is beneficial for the prognosis of patients with metastatic UTUC, whether local tumor resection (HR=0.72, P<0.01) or nephroureterectomy (HR=0.64, P<0.01). Patients with single distant lymph node metastasis have the greatest benefit in nephroureterectomy compared to other specific-site metastases (median survival 19 months vs 8 months). An understanding of distant metastatic patterns and surgical outcomes in patients with UTUC is important in clinical settings and helpful in the design of personalized treatment protocols.